Acute and unexpective course gastroenteritis? Sarcina Ventriculi and Helicobacter pyloriy in german shepherd dog (Canis lupus familiaris) (Gaceta de Ciencias Veterinarias, 2019)
Coexistence between Helicobacter pylori and Sarcina ventriculi in different species, they can cause hyperacute death in patients with gastroenteric and neurological symptoms; therefore they should be taken into account as an etiological agent in the differential diagnoses that are proposed, in this way to be able to treat with the appropriate antibiotic therapy, avoiding a fatal outcome in patients as happened in the case of a dog German Shepherd (Canis lupus familiaris), which is presented in this clinical case.
Keywords: Helicobacter pylori; Sarcina ventriculi; gastroenteric; neurological